Thermal Data of Perfluorinated Carboxylic Acid Functionalized Aluminum Nanoparticles - Nathan J. Weeks; Bradley Martin; Enrique Gazmin; Scott T. Iacono (Data, 2022)
Improving the performance of composite energetic materials comprised of a solid metal fuel and a source of oxidizer (known as thermites) has long been pursued as thermites for pyrolant flares and rocket propellants. The performance of thermites, involving aluminum as the fuel, can be dramatically improved by utilizing nanometer-sized aluminum particles (nAl) leading to vastly higher reaction velocities, owing to the high surface area of nAl. Despite the benefits of the increased surface area, there are still several problems inherent to nanoscale reactants including particle aggregation, and higher viscosity composited materials. The higher viscosity of nAl composites is cumbersome for processing with inert polymer binder formulations, especially at the high mass loadings of metal fuel necessary for industry standards. In order to improve the viscosity of high mass loaded nAl energetics, the surface of the nAl was passivated with covalently bound monolayers of perfluorinated carboxylic acids (PFCAs) utilizing a novel fluorinated solvent washing technique. This work also details the quantitative binding of these monolayers using infrared spectroscopy, in addition to the energetic output from calorimetric and thermogravimetric analysis.